Peran “Konten Makeover” pada Tiktok Rucas.co dalam Membangun Loyalitas Merek - Khairunnisa, Julia; Pandrianto, Nigar (Prologia, 2025)
Tiktok is one of the most popular social media with total users ranking in the top four. Implementing a good strategy in promotional activities on Tiktok can increase Brand Loyalty. This study analyzes “makeover” content on Tiktok as a strategy in building Brand Loyalty in Rucas.co. This research was carried out with a qualitative analysis that referred to the discourse analysis (DA) method from Teun A. Van Dijk. Data was obtained through observation and identification of content through video narratives and social media trends. Content analysis is focused on content that includes makeovers of foreigners with high audience engagement based on the highest number of likes, views and comments. The amount of content taken for analysis was five contents. The research results show that the role of the Rucas brand's collaborative content with street strangers (parking attendants & scavengers) succeeded in providing a strong experience or emotional attachment to the audience with strategies including selecting collaborators/influencers, marketing virality with visualization and storytelling of video content which was then built with the right context. humanist. Tiktok merupakan salah satu media sosial yang paling populer dengan total pengguna menempati urutan empat besar. Penerapan strategi yang baik dalam kegiatan promosi di Tiktok dapat meningkatkan Brand Loyalty. Penelitian ini menganalisis konten “makeover” di Tiktok sebagai strategi dalam membangun Brand Loyalty pada Rucas.co. Penelitian ini dilakukan dengan analisis kualitatif yang mengacu metode analisis wacana atau Discourse Analysis (DA) dari Teun A. Van Dijk. Data diperoleh melalui observasi dan identifikasi konten melalui narasi video serta tren media sosial. Analisis konten difokuskan pada konten yang menyertakan makeover orang asing dengan engagement penonton yang tinggi berdasarkan jumlah likes, views dan comment terbanyak. Jumlah konten yang diambil untuk dianalisis yaitu lima konten. Hasil penelitian menunjukkan bahwa peran konten kolaborasi brand Rucas dengan orang asing jalanan (tukang parkir & pemulung) berhasil memberikan pengalaman atau keterikatan emosional yang kuat kepada penonton dengan strategi diantaranya pemilihan kolaborator/influencer, viralitas marketing dengan visualisasi serta storytelling konten video kemudian dibangun dengan konteks yang humanis.